2009
DOI: 10.5194/aab-52-79-2009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the bovine <i>GHRL</i> gene (Short Communication)

Abstract: Bovine ghrelin, a 27 amino acid peptide, has been identified in oxyntic glands of the abomasum. It is an endogenous ligand for growth hormone secretagogue receptor and stimulates food intake and growth hormone secretion. The bovine GHRL gene was completely sequenced and consists of five exons and four introns. Like mouse and human GHRL genes, we found that the bovine GHRL gene also contains a first non-coding exon of 21 bp. The bovine GHRL gene codes for 116 amino acid peptide named preproghrelin which contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Meanwhile, the only high polymorphic region was found to be restricted on the fourth intron. In consonance with our findings, it was shown that all the observed GHRL SNPs were located in intronic or in the non-coding regions as in the water buffaloes [3], cattle [20], and goats [21]. However, this study reported the highly intronic variations of the GHRL 262-bp fragment and the lack of any polymorphism in the GHRL 113-bp fragment across the ovine and caprine species.…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, the only high polymorphic region was found to be restricted on the fourth intron. In consonance with our findings, it was shown that all the observed GHRL SNPs were located in intronic or in the non-coding regions as in the water buffaloes [3], cattle [20], and goats [21]. However, this study reported the highly intronic variations of the GHRL 262-bp fragment and the lack of any polymorphism in the GHRL 113-bp fragment across the ovine and caprine species.…”
Section: Discussionsupporting
confidence: 90%
“…SNP in intron 3 of GHRL has also been analyzed on other cattle breeds and the similar frequency of the G allele was found: 0.15, 0.12, 0.03, 0.19 and 0.24 for Angus, Charolais, Holstein, Belgian Blue and Simmental cattle, respectively [4,11]. In the bovine ghrelin gene itself, eight SNPs have been detected so far.…”
Section: Discussionmentioning
confidence: 87%
“…In the bovine ghrelin gene itself, eight SNPs have been detected so far. All of them are located in the non-coding parts of the gene [4]. Also in goats, SNP in the GHRL gene was found and it is also located in the non-coding sequence [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GHRL gene in cattle is composed of five exons and four introns, with exons 1, 2, 3, 4, and 5 having lengths of 21, 134, 114, 109, and 154 bp, respectively, while the coding region contains exons 2, 3, 4 and 5 (partially) (Colinet et al, 2009). The GHRL gene is located on chromosome 22 in cattle (Wajnrajch et al, 2000) and is a candidate gene for the identification of molecular markers, because it induces food ingestion, secretion of GH, adiposity, and susceptibility to obesity (Sun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%